The hydrogen absorption behavior of high Nb contained titanium aluminides under high pressure and temperature. (10th August 2016) - Chen, Ruirun; Ma, Tengfei; Sun, Zhiping; Guo, Jingjie; Ding, Hongsheng; Su, Yanqing; Fu, Hengzhi
Abstract: The hydrogen absorption behavior of Ti44Al6Nb and Ti44Al8Nb (at.%, similarly hereinafter except the special illustration) alloys with lamellar structure is investigated under hydrogen pressure range from 0.1 MPa to 10.0 MPa and at temperature between 573 K and 773 K with a volumetric apparatus. The experimental results show that the hydrogen absorption rate increases with increasing of temperature at temperature range of 573K–773 K under hydrogen pressure of 8.0 MPa. The diffusion coefficient was calculated based on Fick's second law at high temperature and pressure, the diffusion coefficient of hydrogen in Ti44Al6Nb alloy is 4.28 × 10 −4  cm 2 /s, 5.51 × 10 −4  cm 2 /s, 8.76 × 10 −4  cm 2 /s under 8.0 MPa at temperatures 573 K, 673 K, 773 K, respectively. The quantitative relationship between hydrogen pressure and hydrogen content was obtained from curve fitting, hydrogen content increases with increasing of the pressure and temperature. Hydrogen content is also influenced by the volume fraction of α2 and B2 phase, which increases with increasing of α2 and B2 phase. Graphical abstract: Hydrogen absorption in TiAl–Nb based alloy with increasing of pressure at temperature range of 573 K to773 K. Highlights: Hydrogen absorption rate increases with increasing of temperature. A new method is put forward for calculation the diffusion coefficient of hydrogen. Hydrogen diffused through grain boundaries and α2 /γ interlamellar regions under high temperature and pressure. Hydrogen content increases with increasing of temperature, pressure and the volume fraction of α2 phase and B2 phase.